(untitled) (Journal of the College of Basic Education, 2026)
In order to comprehend the relationship between language and the environment, this study focuses on revisiting earlier studies in the fields of stylistics and eco-critical discourse analysis, emphasizing the theoretical and methodological techniques utilized in literary and linguistic text analysis. The study intends to determine how texts reflect environmental attitudes and ideas about nature and animals, as well as how language is used to illustrate conflicts between people and non-humans. It looks at how scholars find language patterns that represent environmental exploitation or nature appreciation activities and how these strategies affect readers’ environmental consciousness. It explores how stylistic decisions made at various levels influence human-nature relationships and contribute to eco-critical discourse. Using multi-level linguistic analysis at the phonological, grammatical, semantic, and discourse levels, this study employs a qualitative stylistic and eco-critical methodology. The paper examines current research gaps in this area, such as the neglect of non-human voices or specific environmental aspects. By combining multi-level stylistic analysis with eco-critical discourse in the examination of environmental narratives, this study advances eco-stylistic research.